Membrane Dynamics and Organization of the Phagocyte NADPH Oxidase in PLB-985 Cells - Joly, Jérémy; Hudik, Elodie; Lecart, Sandrine; Roos, Dirk; Verkuijlen, Paul; Wrona, Dominik; Siler, Ulrich; Reichenbach, Janine; Nüsse, Oliver; Dupré-Crochet, Sophie (Frontiers in Cell and Developmental Biology, 2020)
Neutrophils are the first cells recruited at the site of infections, where they phagocytose the pathogens. Inside the phagosome, pathogens are killed by proteolytic enzymes that are delivered to the phagosome following granule fusion, and by reactive oxygen species (ROS) produced by the NADPH oxidase. The NADPH oxidase complex comprises membrane proteins (NOX2 and p22phox), cytoplasmic subunits (p67phox, p47phox, p40phox) and the small GTPase Rac. These subunits assemble at the phagosomal membrane upon phagocytosis. In resting neutrophils the catalytic subunit NOX2 is mainly present at the plasma membrane and in the specific granules. We show here that NOX2 is also present in early and recycling endosomes in human neutrophils and in the neutrophil-like cell line PLB-985 expressing GFP-NOX2. In the latter cells, an increase in NOX2 at the phagosomal membrane was detected by live-imaging after phagosome closure, probably due to fusion of endosomes with the phagosome. Using super-resolution microscopy in PLB-985 WT cells, we observed that NOX2 forms discrete clusters in the plasma membrane. The number of clusters increased during frustrated phagocytosis. In PLB-985NCF1GT cells that lack p47phox and do not assemble a functional NADPH oxidase, the number of clusters remained stable during phagocytosis. Our data suggest a role for p47phox and possibly ROS production in NOX2 recruitment at the phagosome.